El judo como estrategia pedagógica en el desarrollo de las relaciones sociales de los estudiantes del Liceo Naval - Saltos Aldaz, Luis Alberto (2018)
The main idea of this project is to improve relationships in the school through Judo. This study is leading the way by different departments such as Physical Culture in coordination with the general inspectors ‘office and Students Counseling groups. The study was carried out amoung of 24 students between 8 and 17 ages from different grades and curses at Liceo Naval Guayaquil. This investigation was made using methodological strategies of qualitative orientation: a questionnaire about social variables and interactions in the dojo; the field diary of the teacher and the interview. To carry out this proposal, the socio-critical paradigm focused on "action research" is used, strategies that combine theory and praxis and serve to improve the educational and social system. The objective of this Project was to promote physical activity through the program "Judo as a pedagogical strategy" that allows the solution of social conflicts and strengthen the processes of integration and socialization through sport. The introduction of socializing games of cooperative way, using all different variants and modalities, it was transversal in all parts of the structure of the sessions. The learning styles stand out: solving problems, detection guided and direct commanding. Finally it was achieved the pedagogical strategy to prevent social conflicts in and out of the classroom, promoting integration and socialization processes through the sport of combat, based on the original ideology of the Founder of Judo (Jigoro Kano) to the contribution of well-being Social.